2009
DOI: 10.1039/b912782h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of fluorescent enone derived α-amino acids

Abstract: The development of a facile and general method for the preparation of enone derived alpha-amino acids is described. The key step involves a Horner-Wadsworth-Emmons reaction between an aspartic acid derived beta-keto phosphonate ester and a range of aldehydes resulting in the formation of highly functionalised alpha-amino acids in good yields. An efficient two-stage deprotection process using mild conditions was developed to give the parent alpha-amino acids. Application of this methodology has produced a novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 34 publications
1
30
0
Order By: Relevance
“…It must be noted that a sterically hindered trityl protecting group is necessary for regioselective addition to the ester of the side chain (Scheme 66). [85][86][87] These authors also reported the synthesis of optically active b-pyridyl . The removal of both the amine and carboxylic acid protecting groups was performed to give the free amino acids.…”
Section: Phosphorus Linked To Carbon In the D-positionmentioning
confidence: 99%
“…It must be noted that a sterically hindered trityl protecting group is necessary for regioselective addition to the ester of the side chain (Scheme 66). [85][86][87] These authors also reported the synthesis of optically active b-pyridyl . The removal of both the amine and carboxylic acid protecting groups was performed to give the free amino acids.…”
Section: Phosphorus Linked To Carbon In the D-positionmentioning
confidence: 99%
“…The reactions were carried out as described for 12 1H, m, 2-H To a solution of methyl (2S)-2-[(benzyloxycarbonyl)amino]-3-(1′,5′-diphenyl-1′H-pyrazol-3′-yl)propanoate (17) (0.09 g, 0.19 mmol) in methanol and water (5 mL, 7 : 3) was added cesium carbonate (0.08 g, 0.25 mmol). The reaction mixture was stirred at room temperature for 16 h before concentrating in vacuo.…”
Section: Methyl (2s)-2-[(benzyloxycarbonyl)amino]-3-[5′-(naphthalen-2mentioning
confidence: 99%
“…10a Recently, we reported an efficient approach for the preparation of a rare class of α-amino acid with enone side chains. 12 In exploring the reactivity and application of these amino acids, we discovered that these could undergo selective 6-endotrig cyclisations for the synthesis of 4-oxopipecolic acids, 13 and had potential as biological probes with the preparation of a highly fluorescent 4-dimethylamino-1-naphthyl enone analogue. 12 Despite these advances, we found that on long-term storage, the enones were prone to decomposition.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 All reagents and starting materials were obtained from commercial sources and used as received. All dry solvents were purified using a solvent purification system.…”
Section: Methodsmentioning
confidence: 99%